ANTIPYRETIC ACTIVITY OF CENTELLA (CENTELLA ASIATICA (L.) URBAN) HERB IN VACCINE INDUCED MICE - SAPTARINI, NYI MEKAR; KARTIKAWATI, ENDAH (International Journal of Applied Pharmaceutics, 2021)
Objective: This study aimed to determine the antipyretic activity of the infusion of centella (Centella asiatica (L.) Urban) herb, based on empirically usage of Indonesian people. Methods: Antipyretic activity assay was conducted to Swiss-Webster mice, which induced by diphtheria-pertussis-tetanus (DPT) vaccine with paracetamol as positive control. Results: Centella herb was contained tannins, flavonoids, monoterpenoids, sesquiterpenoids, triterpenoids, steroids, and saponins. The antipyretic activity of centella infusion has a ratio 1:44.6, compare to paracetamol. Conclusion: Antipyretic activity of centella herbs was predicted due to its secondary metabolites.